1999
DOI: 10.1007/pl00006449
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecies Analysis: Comparison of ITS Sequence Data and Gene Intron Sequence Data with Breeding Data for a Worldwide Collection of Gonium pectorale

Abstract: The morphologically uniform species Gonium pectorale is a colonial green flagellate of worldwide distribution. The affinities of 25 isolates from 18 sites on five continents were assessed by both DNA sequence comparisons and sexual compatibility. Complete sequences were obtained (i) for the internal transcribed spacer ITS-1 and ITS-2 regions of ribosomal DNA and (ii) for each of three single-copy spliceosomal introns, two in a small G protein and one in the actin gene. ITS sequences appeared to homogenize suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 18 publications
(33 reference statements)
2
34
0
1
Order By: Relevance
“…There has been a series of previous efforts to resolve the phylogeny of the Volvocaceae. These include a cladistic analysis of morphological data by Nozaki (8) and sequence comparisons of variable regions of nuclear ribosomal genes (rSSU and rLSU) (9, 10), of gene introns (1,11), and of the plastid-encoded rbcL and atpB genes (summarized in ref. 12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a series of previous efforts to resolve the phylogeny of the Volvocaceae. These include a cladistic analysis of morphological data by Nozaki (8) and sequence comparisons of variable regions of nuclear ribosomal genes (rSSU and rLSU) (9, 10), of gene introns (1,11), and of the plastid-encoded rbcL and atpB genes (summarized in ref. 12).…”
Section: Discussionmentioning
confidence: 99%
“…I sequenced the internal transcribed spacer (ITS) sequence ITS-1 and ITS-2 regions of the nuclear rRNA cistron because previous results with Volvocales have demonstrated that they are Ͼ10-fold more variable than rRNA genes yet are homogenized by unknown mechanisms with very high frequency, such that they behave essentially as a single locus despite the presence of Ͼ100 tandem copies in a genome (1). Furthermore, knowledge of the ITS RNA transcript secondary structure (2, 3) is valuable in guiding alignment among more distantly related taxa.…”
mentioning
confidence: 99%
“…The mud came from two small pools of freshwater adjacent to a large hypersaline lake (Cha-gan-nur, Hao-tong-yin) in Inner Mongolia. Mating types of Mongolia 4 and 1 were determined by crossing with Alaska 1 and 2 strains (Fabry et al 1998), whereas those of Kaneko3 and -4 were tested against Mongolia 4 and 1.…”
Section: Experimental Organisms and Culture And Mating Methodsmentioning
confidence: 99%
“…Of these, the first internal transcribed spacer (ITS1) diverges rapidly between closely related species, which has enabled it to be utilized for phylogenetic studies at or below the species level (e.g., Fabry et al 1999;Rodriguez-Perez et al 2006). Despite some success at investigating population relationships, intraindividual variation is common for this spacer, and unless a high level of sequence homogeneity has been maintained within species, it can obscure the resolution of phylogenetic trees (Miller et al 1996;Famà et al 2000).…”
Section: Introductionmentioning
confidence: 99%